To the people of New-York. : Though the association lately set on foot, was on pretence of keeping the peace of the city, yet it is evident that it has a direct tendency to disturb that peace . - Citizen (LLMC-digital (Series), 1774)
Opposing the association paper as an approval of the conduct of the British ministry.